Learning to Teach between Theory and Practice: A Project for the Integration of Constructivist Approaches to Teaching in Geographical Higher Education - Neeb, Kerstin (Journal of Geography Education, 2008)
The alarming results of comparative national and international studies have sparked an intense discussion about the learning aptitudes of German pupils and students. The persistent demands for a reorganisation of the German educational system have translated into educational standards which define the required level of skills students should have upon finishing Sekundarstufe I (classes 5 to 10). But what does good instruction at schools and universities look like, especially if it aims to qualify pupils and students for exams and the job market on the one hand and for life in a globalising society on the other hand? In education studies, impulses from pedagogic psychology have resulted in theoretical models which conceptualize learning as an active-constructive activity that occurs in a self-directed and situated fashion. By solving real-life problems practical knowledge can be taught. But to what extent is it possible to realise this pedagogical constructivism in school instruction? What does it mean to teach or learn in a constructivist fashion? In the following, possibilities of applying constructivist instruction will be examined in the context of teacher-training in geography, using the "goal-based scenario". Small groups of university students are instructed to develop, plan, organise and evaluate a field trip for year 5 or year 6 pupils following the human interests. It proposes an inclusion of the concept of relational space in environmental education. This concept is thought to be compatible with action theory, emancipatory approaches of pedagogics and constructivist didactics.